2019
DOI: 10.1002/dc.24250
|View full text |Cite
|
Sign up to set email alerts
|

Risk of malignancy and neoplasia predicted by three molecular testing platforms in indeterminate thyroid nodules on fine‐needle aspiration

Abstract: BACKGROUND The management of thyroid nodules with indeterminate cytology is challenging. Recently, molecular testing on fine‐needle aspirates (FNAs) has been advocated to determine whether clinical follow‐up or surgery is warranted for patients. Three different testing platforms were performed on aspirates from our institution (Afirma Thyroid FNA Analysis, RosettaGX Reveal, and Interpace ThyGenX/ThyraMIR). This study compares their diagnostic efficacy. METHODS We conducted a retrospective analysis of indetermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 56 publications
1
27
0
5
Order By: Relevance
“…Regarding molecular panels, 25 studies evaluated the diagnostic performance of the Afirma GEC ( 8 , 16 , 17 , 40 , 47 54 , 56 58 , 61 , 63 , 64 , 66 70 , 72 , 76 , 77 ), and four articles reported the Afirma GSC ( 16 , 17 , 57 , 70 ). Thyroseq versions 2 and 3 were found in nine ( 11 , 15 , 58 , 59 , 61 , 62 , 71 , 73 , 75 ) and four papers ( 14 , 55 , 59 , 65 ), respectively, while ThyraMIR/ThyGenX ( 23 , 67 , 68 ) and ResettaGX Reveal ( 61 , 67 , 68 ) were explored in three studies, respectively. The panels with the fewest assessments were ThyraMIR/ThyGeNEXT and miRInform ( 23 , 74 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding molecular panels, 25 studies evaluated the diagnostic performance of the Afirma GEC ( 8 , 16 , 17 , 40 , 47 54 , 56 58 , 61 , 63 , 64 , 66 70 , 72 , 76 , 77 ), and four articles reported the Afirma GSC ( 16 , 17 , 57 , 70 ). Thyroseq versions 2 and 3 were found in nine ( 11 , 15 , 58 , 59 , 61 , 62 , 71 , 73 , 75 ) and four papers ( 14 , 55 , 59 , 65 ), respectively, while ThyraMIR/ThyGenX ( 23 , 67 , 68 ) and ResettaGX Reveal ( 61 , 67 , 68 ) were explored in three studies, respectively. The panels with the fewest assessments were ThyraMIR/ThyGeNEXT and miRInform ( 23 , 74 ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies (n = 32) evaluate a single molecular panel, of which 18 articles reported Afirma GEC alone ( 8 , 40 , 47 54 , 56 , 63 , 64 , 66 , 69 , 72 , 76 , 77 ), nine papers assessed second or third version of Thyroseq NGS ( 11 , 14 , 15 , 55 , 62 , 65 , 71 , 73 , 75 ) and lastly, ThyraMIR/ThyGeNEXT, ThyraMIR/ThyGenX, miRInform and RosettaGX Reveal were each approached in a study ( 21 , 23 , 60 , 74 ). Among the nine studies that measured up more that two molecular panels, four paper compared Afirma GEC and GSC ( 16 , 17 , 57 , 70 ), two manuscripts reported a comparison between Afirma GEC and Thyroseq v2 ( 58 , 61 ), two papers investigated the diagnostic performance of Afirma GEC, RosettaGX and Interpace MPT ( 67 , 68 ) and Jug et al. ( 59 ) compared the two last versions of Thyroseq NGS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, some cytologists have introduced the term “risk of neoplasia” (RON) for thyroid FNA specimens . Using this measure, the identification of a neoplastic nodule (including follicular adenoma as well as carcinoma) rather than a hyperplastic nodule or normal thyroid tissue is counted as a “success.” Indeed, much of the literature that predated TBSRTC and the introduction of ROM was reported in just such a manner.…”
mentioning
confidence: 99%